The Influence of Parental Bonding on Depression, Shame, and Anger among Thai Middle School Children, Being Mediated by Peer Victimization (Victim of Bullying): A Path Analytical Study - Luanpreda, Pak; Verma, Parvathy (Scholar: Human Sciences, 2016)
Research has identified that victims of school bully often experiencing emotional distress and parental bonding as the factor for children to cope with these feeling better. As an attempt to understand better how does parental bonding impacts on victims’ state of emotion, thecurrent study explore the direct and indirect influences of perceived parental bonding (caring and overprotection), being mediated by peer victimization (victim of bullying), on the emotive states of depression, shame, and anger among Thai middle school children. This quantitative study employed a correlational design via path modeling to test the stated research hypotheses. The results of this study were based on the responses of participants to a six-part survey questionnaire. This investigation involved a sample of 180 Thai school children aged between 11 and 15 years to provide baseline measurements of the targeted relationships to meet the objectives of this study. The findings indicate that the lower level of parental bonding shows a higher level of depression among children. Also, victims of bully report to develop higher level of depression and anger. Furthermore, there is no significant gender difference in peer victimization.